Do remittances increase borrowing? - Christian Ambrosius; Alfredo Cuecuecha (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2014)
While recent literature has pointed out that migrants remittances have a positive impact on savings with financial institutions, findings with respect to access to and the use of loans have been ambiguous. This paper investigates whether the reception of remittances facilitates taking up loans from formal or informal sources among Mexican households and finds positive and statistically significant effects of remittances on borrowing and on the existence of debts. We address methodological concerns of selection bias and reverse causality through household fixed effects and an instrumental strategy that exploits distance to train lines and labor market conditions in the US as exogenous determinants of remittances.
Keywords: F24; D14; I15; O12; 330